Genetic analysis of wild walnuts in Xinjiang based on whole-genome resequencing - Liu, Yuyu; Zhang, Ping; Wang, Zhuli; Fu, Jilong; Han, Jing; Gao, Yihang; Feng, Zhibo (Frontiers in Plant Science, 2025)
IntroductionAs a treasured wild plant resource in the Tian shan Mountains, the genetics and evolutionary relationships of Xinjiang wild walnuts (Juglans regia L.) are of great interest for both walnut conservation and crop improvement.MethodsIn this study, a total of 200 walnut accessions, including a core germplasm collection of wild walnuts from Xinjiang and local walnut landraces and cultivars, were selected for whole-genome resequencing, with the final dataset supplemented with 24 other publicly available genomic datasets for other walnut taxa.ResultsAcross all samples, there was evidence of four ancestral genetic populations, with three of these represented in the samples from Xinjiang. The Xinjiang wild walnuts form an independent evolutionary clade with low genetic diversity, which was further differentiated into six subgroups, and showed significant genetic differentiation from the cultivated accession. The walnut cultivars and landraces showed mixed ancestry, being assigned to two ancestral populations not represented in the wild walnuts. The Gongliu Wild Walnut Valley served as one of the refugia during the Last Glacial Maximum (LGM) for Tertiary relict species. The unique topography of the Ili River Valley in Xinjiang, along with the relatively isolated geographical location of the Walnut Valley, may have collectively facilitated the formation of a relatively isolated “genetic island” pattern in the Xinjiang wild walnuts. Selective sweep analysis identified 20 genes under selection, including CYP450 genes closely associated with disease resistance and NF-YB3 genes involved in cold stress and other adaptive responses.DiscussionA new framework is needed to reconceptualize the genetic relationships of Xinjiang wild walnuts with other germplasms, clarifying their continuous role throughout the evolutionary continuum from glacial refugium to domestication and modern breeding.